Пердика, Атина и коринтската парадогма - Саракински, Војислав (Филозофски факултет, Скопје, 2017)
This paper puts to test the virtually axiomatic historical paradigm of the inevitability of the clash between Sparta and Athens as carriers of two opposing political and cultural concepts, and hence the inevitability of the Peloponnesian War itself. This ultimately leads us to the question of the real goal of the Athenian ventures in the late 430s, namely, whether the Athenian policy as a whole was directed against Corinth and Sparta, or if there was another venture that the Athenians had in mind, a venture which unfortunately ignited the fire of the Peloponnesian War. We offer a detailed look at several issues: (1) whether the Athenians are conducting preparations for war at that time, (2) which war they actually have in mind, (3) whether Thucydides reveals their immediate plans, (4) if he does, indeed, whether they are aimed at Corinth and Sparta, and (5) if he does not, what are the reasons for it. Several important details suggest that the Athenian foreign policy was far from showing the uniformity we expect to find; that the Athenian policies rather consisted of a mosaic of small, opportune political decisions with hardly any ideological deposit; and that the hostilities in the North, which presented the main grievance leading to the Peloponnesian War, were not necessarily aimed at Corinth and certainly not at Sparta. One could argue that the Poteidaian affair was meant to be a part of a projected short, limited and controlled “Macedonian War”, supposed to begin and to end in a single battle season, a war which would once and for all secure both the primary and the alternative sources of Athenian timber supply. However, not least because of the paradigm of a Peloponnesian War that emerges from the realm of ananke – a paradigm seemingly modern, but actually rooted in classical historiography – the “Macedonian war” will certainly continue to be absent from historical literature. And this, it would seem, is a perfect reminder that historical paradigms need to be constantly checked and redefined.
Perdiccas, Athens and the Corinthian Paradogma